Tourism Awareness Socialization For Students At Of Madrasah Aliyah Industri Al-Jabar, Batam City - Thandzir, Moh.; Dailami; Ilham, Wahyudi; Sukmamedian, Haufi; Pratama, Tito; Yusuf, Abd Rahmad (JURNAL KEKER WISATA, 2025)
is an initiative aimed at increasing awareness and understanding among the public and stakeholders regarding sustainable tourism practices. This program emphasizes education and information on the importance of preserving the environment, respecting local cultures, and supporting the economies of communities involved in the tourism industry. Through education, training, and advocacy, this initiative seeks to encourage responsible behavior from all parties involved in tourism activities, with the goal of creating long-term positive impacts on tourism destinations as a whole